2022
DOI: 10.3390/biomedicines10061284
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Pancreatic Cancer: Recent Progress in Epidemiology, Mechanisms and Bariatric Surgery

Abstract: More than 30% of people in the United States (US) are classified as obese, and over 50% are considered significantly overweight. Importantly, obesity is a risk factor not only for the development of metabolic syndrome but also for many cancers, including pancreatic ductal adenocarcinoma (PDAC). PDAC is the third leading cause of cancer-related death, and 5-year survival of PDAC remains around 9% in the U.S. Obesity is a known risk factor for PDAC. Metabolic control and bariatric surgery, which is an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…The systematical evaluation of epidemiologic evidence about the causal relationship between a high BMI and pancreatic cancer among adults showed that the relative risk was 1.071 (95%CI = 0.999 to 1.154) in males and 1.092 (95%CI = 1.037 to 1.144) in females [28]. Although etiopathogenetic mechanisms that would explain the link between a high BMI and pancreatic cancer were not fully understood, some authors suggested that pancreatic fatty infiltration, chronic inflammation, altered cellular metabolism, hormone dysregulation, microbial dysbiosis, or immune cell infiltration may be involved in pancreatic carcinogenesis [29,30]. It is known that obesity favors the release of pro-inflammatory cytokines such as tumor necrosis factor α and Interleukin-6, which are linked to the development of inflammation, and the onset of cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…The systematical evaluation of epidemiologic evidence about the causal relationship between a high BMI and pancreatic cancer among adults showed that the relative risk was 1.071 (95%CI = 0.999 to 1.154) in males and 1.092 (95%CI = 1.037 to 1.144) in females [28]. Although etiopathogenetic mechanisms that would explain the link between a high BMI and pancreatic cancer were not fully understood, some authors suggested that pancreatic fatty infiltration, chronic inflammation, altered cellular metabolism, hormone dysregulation, microbial dysbiosis, or immune cell infiltration may be involved in pancreatic carcinogenesis [29,30]. It is known that obesity favors the release of pro-inflammatory cytokines such as tumor necrosis factor α and Interleukin-6, which are linked to the development of inflammation, and the onset of cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated triglyceride levels and reduced HDL-c are the components of MetS. Previous studies on dyslipidemia and the risk of PC produced controversial results ( 36 , 38 , 39 ). In the present study, no evidence of increased risk of developing PC due to high triglyceride levels was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying modifiable and non-modifiable risk factors for PDAC within UKBB emphasises the importance of addressing those with the potential to reduce the risk of PDAC if adjusted accordingly [ 26 ]. Modifiable covariables and potential confounders that were measured at baseline were selected for inclusion in the models based on their established association with PDAC, and included: obesity (measured by Body Mass Index (BMI) [ 28 ]), weight change in the previous 12 months [ 33 ], tobacco smoking (never, ex, current and <20/day, and current and ≥20/day) [ 34 , 35 ], alcohol intake (never, special occasions, one to three times/month, one to two times/week, three to four times/week, daily) [ 36 , 37 ] and processed meat consumption (never, less than once a week, once a week, two to four times per week, and five or more times per week) [ 38 ]. The nonmodifiable variables ethnic background (White, Mixed, Asian or Asian British, Black or Black British, Chinese, Other ethnic group) [ 39 ], age and sex were also included in models.…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains unclear whether there is an association between conventional HbA1c categories and incident PDAC among people without previously diagnosed DM. It is also uncertain if the strength of the association between NODM and subsequent PDAC is independent of obesity, which is associated with both PDAC [ 28 ] and DM [ 29 , 30 ]. Unintentional weight loss is also associated with both conditions (when glucose levels are very high prior to a diagnosis of DM) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%